OsAM1 is required for leptotene-zygotene transition in rice - Che, Lixiao (Nature Publishing Group, 2011)
The events occurring at the onset of meiosis have not been fully elucidated. In the present study, OsAM1 was identified in rice (Oryza sativa L.) by map-based cloning. OsAM1, a homolog of Arabidopsis SWI1 and maize AM1, encodes a protein with a coiled-coil domain in its central region. In the Osam1 mutant, pollen mother cells are arrested at leptotene, showing that OsAM1 is required for the leptotene-zygotene transition. Immunocytological analysis revealed that OsAM1 exists as foci in early prophase I meiocytes. Very faint OsREC8 foci persisted in the Osam1 mutant, indicating that OsAM1 is not required for the initial meiotic recruitment of OsREC8. In the absence of OsAM1, many other critical meiotic components, including PAIR2, ZEP1 and OsMER3, could not be correctly installed onto chromosomes. In contrast, in pair2, Osmer3 and zep1 mutants, OsAM1 could be loaded normally, suggesting that OsAM1 plays a fundamental role in building the proper chromosome structure at the beginning of meiosis.